TOWARD THE ESTABLISHMENT OF THE TOOLS FOR MONITORING COASTAL ENVIRONMENTS UTILIZING GENE RESPONSE IN ORYZIAS FISHES - Inoue, Koji; Yamamoto, Yu; Yusof, Shahrizad; Dung, Le Quang; Arifin, Zainal; Ismail, Ahmad; Kinoshita, Masato (Marine Research in Indonesia, 2013)
Southeast Asia is known as a center of biodiversity of the earth. As economic growth of this region is remarkable, conservation of biodiversity is a top priority issue. For this purpose, it is important to monitor the environmental condition in effective ways. We are trying to detect pollutants in coastal and estuary waters through the expression level of pollutant-responsive genes of rice fishes of the genus Oryzias, widely distributed in Asia. Japanese medaka O. latipes is a useful model because whole genome sequence is available. Javanese medaka O. javanicus and Indian medaka O. dancena, both of which are widely distributed in Southeast Asia and adaptable to seawater, are also potential models. One possible method for pollution monitoring is the use of transgenic fish bearing artificialgene construct containing the pollutant-responsive promoter and a reporter gene. For example, transgenic strains that can detect estrogen-like substances have already been established. It is also probable to detect pollutants by quantifying mRNA or proteins expressed from the pollutant-responsive gene. In any case, the most important point is to identify the gene that responds to specific pollutants. Comprehensive transcriptomic analyses are powerful tool for this purpose. Organotin-responsive genes are being screened at present.